2007
DOI: 10.1007/s12038-007-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decrease in rod bipolar cell density of the human retina: an immunohistochemical study

Abstract: During normal ageing, the rods (and other neurones) undergo a significant decrease in density in the human retina from the fourth decade of life onward.Since the rods synapse with the rod bipolar cells in the outer plexiform layer, a decline in rod density (mainly due to death)may ultimately cause an associated decline of the neurones which,like the rod bipolar cells,are connected to them.The rod bipolar cells are selectively stained with antibodies to protein kinase C-alpha.This study examined if rod bipolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 20 publications
7
36
1
Order By: Relevance
“…Klein et al16 found that in a control group of subjects, arteriolar caliber decreased by 1.0 m/decade and venular caliber decreased by 0.7 m/decade. Retinal cell number has also been reported to decrease with age 17,18,19,20. Harman et al17 found a decrease in neuron number in the retinal ganglion cell layer with increasing age; they estimated that in the macular region, neuronal density decreased by 0.29% per year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Klein et al16 found that in a control group of subjects, arteriolar caliber decreased by 1.0 m/decade and venular caliber decreased by 0.7 m/decade. Retinal cell number has also been reported to decrease with age 17,18,19,20. Harman et al17 found a decrease in neuron number in the retinal ganglion cell layer with increasing age; they estimated that in the macular region, neuronal density decreased by 0.29% per year.…”
Section: Discussionmentioning
confidence: 99%
“…Bipolar cells may also be involved in retinal thinning. Aggarwal et al20 found that after the third decade, rod bipolar cell density starts to decrease. From our analysis we cannot ascertain the source of the retinal thinning not accounted for by loss of RNFL; however, it is likely due to a combination of decreases in vessel caliber and loss of retinal ganglion, photoreceptor, bipolar, and RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in mice and humans have shown that a normally aging retina goes through pathological changes including the formation of ectopic photoreceptor synapses, increased inflammation, and gradual photoreceptor cell degeneration (Aggarwal et al 2007, Eliasieh et al 2007, Fuchs et al 2012, Samuel et al 2011, Terzibasi et al 2009). Similar retinal abnormalities have been observed in retinal degenerative diseases such as age-related macular degeneration (AMD) (Aggarwal et al 2007, Eliasieh et al 2007, Sullivan et al 2007), suggesting a link between the molecular mechanisms of retinal aging and age-dependent retinal diseases. Elucidating the molecular mechanisms causing these age-dependent retinal abnormalities will enhance our understanding of the molecular and cellular changes underlying aging and age-dependent diseases in the retina.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Photoreceptors are the most numerous and metabolically active cells in the retina, with a large number of mitochondria, having high oxygen consumption. The cells of the inner nuclear layer and the ganglion cell layer represent ,10% of the number of photoreceptors, [7][8][9] and thus, additional damage to the inner retina is unlikely to significantly improve clinical efficacy. After a laser burn, the photoreceptor layer is partially replaced by glial tissue.…”
mentioning
confidence: 99%